CHARACTERISTICS OF BALI BEEF THIGH MEAT MARINATED WITH ROBUSTA COFFEE FILTRATE - H. J. B., Liemman,; Oka, A.A.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2024)
The purpose of this research was to knowed effection of robusta coffee filtrate on Bali beef thigh meat and to decide the concentration of the filtrate. The study using a completely CRD with four types of treatment, each repeated five times. The ftreatments were no marination (P0), 5% filtrate from robusta coffee (P1), 10% filtrate from robusta coffee (P2), and 15% filtrate from robusta coffee (P3). The variables which notice included the physical and organoleptic characteristics. The methods used were ANOVA for physical characteristics and non-parametric analysis for organoleptic characteristics. The results circumstances for physical characteristics, the pH from four treatments differed significantly (P<0.05) P0 with P1, P2, P3. Cooking loss differed significantly (P<0.05) with P0 to P1, as well as P0 with P1, P2, and P2 with P3. For organoleptic characteristics, color and tenderness showed differences of significant (P<0.05) with P0 and P1, P2, and P3. It was concluded that a 5% robusta coffee filtrate concentration (P1) provided the best results in influencing the characteristics of marinated Bali beef thigh meat.